Effects of DASH and ketogenic diets on metabolic control in women with polycystic ovary syndrome (Research, Society and Development, 2025)
Polycystic ovary syndrome (PCOS) is an endocrine-metabolic condition that affects women of reproductive age and is characterized by hormonal changes, chronic anovulation and insulin resistance. Given the relevance of dietary interventions in the management of this syndrome, this study aims to carry out a literature review to compare the effects of the DASH and ketogenic diets in women with PCOS, in order to identify which of the two strategies has better results on metabolic and hormonal parameters. The search was conducted in the PubMed, SciELO, Google Scholar and BIREME databases, selecting studies published between 2015 and 2025, in Portuguese, English and Spanish. Descriptors such as "Polycystic ovary syndrome", "Síndrome del Ovario Poliquístico", "Síndrome de Stein-Leventhal", "Dieta ketogênica", "ketogenic diet", "Dieta ketogénica", "DASH dietary" and "Mediterranean diet" were used. The results indicate that both diets have positive effects on insulin resistance, body composition and lipid profile, with the ketogenic diet showing greater efficacy in weight loss and glycemic control, while the DASH diet shows sustainable long-term benefits, especially in cardiovascular aspects. It is concluded that both strategies are promising in the management of PCOS, but that it is necessary to individualize the approach according to the profile and clinical response of each patient.